CHARACTERIZING OF ONGGOK FLOUR USING THREE DIFFERENT DRYING METHODS - Sari, Marinda; -, Warji; Novita, Dwi Dian; -, Tamrin (The University of Lampung, 2013)
The processing of cassava becoming tapioca flour will produce solid fiber waste called as onggok. Onggok can be used as raw material for making onggok flour. One of the processing steps on the producing of onggok flour is drying. In common practice, solar dryer is used but it takes long time and strongly depends on weather. The hybrid dryer (solar electrical energy), solar radiation dryer, and electrical dryer would be used in this research. The aims of this study were to determine and to compare whiteness degree, the degree of acidity (pH), and the characteristics of onggok flour (color and aroma) and its organoleptic justification of onggok flour dryed by the three different drying methods. The results showed that drying process under solar radiation dryer produced onggok flour at better color compared with the others, drying process using electrical dryer produced onggok flour at better aroma compared with the others, the best product based on organoleptic tests was onggok flour dried by electrical dryer with color criteria a little white, the aroma criteria slightly cassava aromaed, and overall acceptance a bit like. Keywords: Onggok flour, drying, aroma, flour color